N-Methyl-D-Aspartate (NMDA) Antagonists-S(+)-ketamine, Dextrorphan, and Dextromethorphan-Act as Calcium Antagonists on Bovine Cerebral Arteries - Kamel, Ihab R.; Wendling, Woodrow W.; Chen, Dong; Wendling, Karen S.; Harakal, Concetta; Carlsson, Christer L (Journal of Neurosurgical Anesthesiology, 2008)
Ketamine an intravenous anesthetic and a major drug of abuse, is a noncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist. Ketamine's enantiomer. S(+)-ketamine, acts stereoselectively on neuronal NMDA receptors. The purpose of this in vitro study was to compare the direct effects of S(+)-ketamine. 2 other noncompetitive NMDA receptor antagonists (dextrorphan and dextromethorphan), and the calcium entry blocker nimodipine on the cerebral vasculature, using bovine middle cerebral arterics as an experimental model. Arterial rings were mounted in isolated tissue chambers equipped with isometric tension transducers to obtain pharmacologic dose-response curves. In the absence of exogenous vasoconstrictor, the NMDA antagonists or nimodipine had negligible effects oil cerebral arterial tone. When rings were preconstricted with either potassium or the stable thromboxane A(2) mimetic U46619. the NMDA antagonists and nimodipine each produced dose-dependent relaxation. Prior endothelial stripping had no effect on subsequent drug-induced relaxation of K+-constricted rings. In Ca2+-deficient media containing either potassium or U46619. the NMDA antagonists and nimodipine each produced competitive inhibition of subsequent Ca2+ induced constriction. In additional experiments, arterial strips were mounted in isolated tissue chambers to directly measure calcium uptake, using (45)calcium (Ca-45) as a radioactive tracer. The NMDA antagonists and nimodipine each blocked potasium-stimulated or U46619-stilmulated Ca-45 uptake into arterial strips. These results indicate that S(+)-ketamine, dextrorphan, arteries by acting as calcium antagonists; they all inhibit Ca-45 uptake through both potential-operated (potassium) and receptor-operated (U46619) channels in cerebrovascular smooth muscle.
Keywords: calcium channel; L-type; nimodipine; dextromethorphan; S(+)-ketamine; dextrorphan; vascular smooth muscle; cattle